Dr. José Lasen — Deep Plane Facelift — Santiago - Lasen, José (DEEPPLANE™, 2026)
Surgeon profile record for Dr. José Lasen, practicing in Santiago, Chile. Tracked in the DEEPPLANE™ directory of listed deep plane facelift specialists. Published under CC-BY-4.0.
DPID-003095; accessed 2026-08-14; CC-BY-4.0
Keywords: deep plane facelift; facial plastic surgery; rhytidectomy; SMAS; chile; santiago